(untitled) (Práxis Educativa, 2023)
Neohumanism is a philosophy propounded by Prabhat Rainjan Sarkar which recognizes that humanity needs a new narrative that can provide the inspiration, direction, and tools with which to transform individual selves and collective futures. While acknowledging the vital role that Humanism has played in the historical march towards greater freedom, justice, peace, knowledge, and the utopian vision of a united humanity, Neohumanism challenges the limitations of Humanism, entangled as it is with the host of power/over tactics that characterize modernity. “Diversifying Universalism” explores Neohumanism and Neohumanist education alongside two dominant and contemporary paradigms of a global educational approach aimed at realizing the high ideals of a world united, internationalism and interculturalism, assessing their compatibilities and contrasts, examining their strengths and weaknesses, and suggesting ways in which the integration of certain principles and practices might result in a synthesis that is more comprehensive and effective than any of them alone. Keywords: Neohumanism. Internationalism. Interculturalism.